A Review of Connecting Bioinformatic Techniques to Rheumatoid Arthritis and its Associated Comorbidities - Ranganathan, Yeswanth; Ramesh Kumar, Pritam; Gandhi Paramasivam, Sudhakar; Shankar Krishnan, Ravi (Current Rheumatology Reviews, 2025)
Rheumatoid Arthritis (RA) is a progressive autoimmune condition inflicting serious threats to people’s life and health by causing severe pain and joint destruction. It affects not only bones and joints but also causes comorbid conditions and shortens the lifetime. The interactions and synergistic effects of comorbid disease with RA are not yet well studied. Hence, understanding how these conditions will collectively affect the progression and outcome of RA is the current area of research. Identification of RA and comorbidities associated with target genes may uncover diagnosis and treatment methodologies. This review is to provide an overview of the interlinking approach of Rheumatoid Arthritis with its comorbid conditions and its systemic complications using bioinformatic techniques which would be useful to identify the genes and pathways that are in common for both RA and comorbid diseases. It would also emphasize the significance of bioinformatics in comparing the pathological features of RA and comorbid diseases. With the help of bioinformatics, valuable insights into the mechanism underlying Rheumatoid arthritis and comorbid diseases would be better understood.
Keywords: Rheumatoid arthritis